Spinal Cord Injury: Lessons about Neuroplasticity from Paired Associative Stimulation. (June 2020) - Ling, Yan To; Alam, Monzurul; Zheng, Yong-Ping
Paired associative stimulation (PAS) is a noninvasive neuromodulation method with rare cases of adverse effects for the patients with neurological injuries such as spinal cord injury (SCI). PAS is based on the principles of associative long-term potentiation and depression where the activation of presynaptic and postsynaptic neurons correlated in time is artificially induced. Statistically significant improvement in motor functions after applying PAS has been reported by several research groups. With further standardization of the technique, PAS could be an effective treatment for functional rehabilitation of SCI patients. In this review, we have summarized the methods and findings of PAS on SCI rehabilitation to facilitate the readers to understand the potentials and limitations of PAS for its future clinical use.